2011
DOI: 10.1166/jnn.2011.3536
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Particle Shape-Dependent Dynamics in Nanomedicine

Abstract: One of the major challenges in nanomedicine is to improve nanoparticle cell selectivity and adhesion efficiency through designing functionalized nanoparticles of controlled sizes, shapes, and material compositions. Recent data on cylindrically shaped filomicelles are beginning to show that non-spherical particles remarkably improved the biological properties over spherical counterpart. Despite these exciting advances, non-spherical particles have not been widely used in nanomedicine applications due to the lac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
137
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(140 citation statements)
references
References 60 publications
3
137
0
Order By: Relevance
“…It has been observed that AgNPs synthesized from plant extracts are formed in various sizes; mostly 10-100 nm average particle size (APS). Shah et al also reviewed the nanoparticles as nanomedicines [43] . Zhao et al synthesized graphene oxide (GO)/AgNPs/luminol composites with electrochemiluminescence activity for sensitive detection of DNA methyltransferase activity with the APS of 18 nm [44] .…”
Section: Resultsmentioning
confidence: 99%
“…It has been observed that AgNPs synthesized from plant extracts are formed in various sizes; mostly 10-100 nm average particle size (APS). Shah et al also reviewed the nanoparticles as nanomedicines [43] . Zhao et al synthesized graphene oxide (GO)/AgNPs/luminol composites with electrochemiluminescence activity for sensitive detection of DNA methyltransferase activity with the APS of 18 nm [44] .…”
Section: Resultsmentioning
confidence: 99%
“…Recent advances in fabrication technologies have enabled generation of shape-specific microparticles and nanoparticles (8-12). These particles, inspired by the diverse, evolutionarily conserved shapes of pathogens and cells, are being used to study the role of carrier shape on cellular internalization, in vivo transport, and organ distribution (6,11,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).Despite these pioneering studies, there remains a significant knowledge gap in our fundamental understanding of the interplay between nanoscale shape and size on cellular internalization, especially for clinically relevant polymer-based hydrophilic nanoparticles. Most in vivo drug delivery and imaging applications have proposed the use of nanoparticles with hydrophilic "stealth" surfaces [often achieved through poly(ethylene glycol) (PEG)-based surface modifications] as well as neutral to anionic surface charge, primarily to allow longer in vivo circulation time by reducing protein adsorption and rapid clearance by the reticuloendothelial system (2, 24-27).…”
mentioning
confidence: 99%
“…Recent advances in fabrication technologies have enabled generation of shape-specific microparticles and nanoparticles (8-12). These particles, inspired by the diverse, evolutionarily conserved shapes of pathogens and cells, are being used to study the role of carrier shape on cellular internalization, in vivo transport, and organ distribution (6,11,(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…As has been already stated the effect of NV morphology upon its performance in vivo depends upon its ability to permeate various tissues and perform well in the bloodstream, so that it can circulate freely whilst being capable of interacting with its environment and, in particular, vascular tissues. It has been shown from modelling the flow characteristics of elongated particles that they would, in the bloodstream, naturally drift towards the vessel walls and thereby be more suitable for targeting applications due to this intelligent behaviour [18,81,82]. In other work, rod-shaped particles have shown greater transport across intestinal cells compared to their spherical counterparts, both with active targeting (via biotinylation) enhancing their accumulation at the desired cells, laying the foundation for their development towards oral drug delivery applications; however, development of biodegradable NVs that display such morphology is imperative [15].…”
Section: Impact Of Nanovector Morphology On Performance In Vitro and mentioning
confidence: 99%